Perspektif kesetaraan gender Husein Muhammad terhadap Sexual and Reproductive Health and Rights (SRHR) - Elza Ramona; Peppy Angraini; Al Amin (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
In achieving gender equality, the problem of social construction with the growth of patriarchal culture is still the main obstacle to voicing women's rights, including equality of sexual and reproductive rights for women or Sexual and Reproductive Health and Rights (SRHR), hindered by religious interpretations that are still gender biased. Both traditional and rational interpreters adhere to the interpretation that subordinates women. This cannot be separated from the point of view used by the interpreters, the goals, and the social, cultural, economic, and political conditions in which the interpreters live. This patriarchal interpretation is what one pesantren kiai, known as a male feminist, Husein Muhammad, is trying to reconstruct. Born and raised in a pesantren, Husein's background led him to the women's fiqh program (fiqh al-Nisa), which advocates for women's sexual and reproductive rights from an Islamic gender-equitable perspective. Therefore, using a descriptive-analytic method (tick description), this article attempts to look at Sexual and Reproductive Health and rights (SRHR) from the perspective of gender equality promoted by Husein Muhammad.